2001
DOI: 10.1177/03635465010290020601
|View full text |Cite
|
Sign up to set email alerts
|

Instrumented Measurement of Glenohumeral Joint Laxity and its Relationship to Passive Range of Motion and Generalized Joint Laxity

Abstract: The purpose of this study was to objectively characterize in vivo glenohumeral joint laxity using an instrumented shoulder arthrometer. Secondary objectives were to examine the relationship of glenohumeral joint laxity with passive range of motion and generalized joint laxity. Fifty-one recreational athletes with no history of shoulder injury or long-term participation in overhead sports participated in this study. Anterior and posterior laxity data were obtained at displacement forces of 67, 89, 111, and 134 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…A perpetuating cycle in which subtle laxity of the glenohumeral capsule leads to internal impingement (Davidson et al, 1995), further stretching of the inferior glenohumeral ligament (Jobe and Lannotti, 1995;Mihata et al, 2010;Wilk et al, 2009), and subsequently increased humeral head translation is considered part of the process in internal impingement syndrome (Borsa et al, 2005;Chen et al, 1999;Harryman et al, 1990;Krarup et al, 1999;Sauers et al, 2001;Sethi et al, 2004). This shift of the humeral head in an anterior inferior direction pulls the posterior under surface of the cuff with it which it jams against the posterior superior glenoid during the late cocking phase of throwing.…”
Section: Mechanisms Influencing the Subacromial Space Specific To Intmentioning
confidence: 99%
“…A perpetuating cycle in which subtle laxity of the glenohumeral capsule leads to internal impingement (Davidson et al, 1995), further stretching of the inferior glenohumeral ligament (Jobe and Lannotti, 1995;Mihata et al, 2010;Wilk et al, 2009), and subsequently increased humeral head translation is considered part of the process in internal impingement syndrome (Borsa et al, 2005;Chen et al, 1999;Harryman et al, 1990;Krarup et al, 1999;Sauers et al, 2001;Sethi et al, 2004). This shift of the humeral head in an anterior inferior direction pulls the posterior under surface of the cuff with it which it jams against the posterior superior glenoid during the late cocking phase of throwing.…”
Section: Mechanisms Influencing the Subacromial Space Specific To Intmentioning
confidence: 99%
“…23 These differences have also been reported in healthy nonathletes and in nonoverhead athletes. Sauers et al 24 found decreased values for shoulder internal rotation and extension and increased values for external rotation on the dominant side. A group of healthy, right-handed male subjects, ranging from 8 months to 54 years old, presented increased active shoulder internal rotation and extension on the left side.…”
Section: Discussionmentioning
confidence: 95%
“…The development of more objective tools to provide measures in a clinically feasible manner may also be beneficial Sauers et al 2001;Sein et al 2008). However, the clinical implementation of complex mechanical devices is likely to be limited.…”
Section: Discussionmentioning
confidence: 99%